VARIASI KALIMAT TUNGGAL DAN MAJEMUK DALAM WACANA IKLAN MOBIL DI KEDAULATAN RAKYAT [Simple and Compound Sentence Variation in Car Advertising Discourse in Kedaulatan Rakyat] - Aji Prasetyo (TOTOBUANG, 2016)
Sentence variation analysis in this study was an analysis based on variation patterns of single sentence in car advertising discourse based on  word category on verb, including simple sentence with its predicated verb, simple sentence with its predicated adjective, simple sentence with its predicated noun, simple sentence with its predicated prepositional phrase, and simple sentence with its predicated numeral phrase. Variation patterns analysis of compound sentence in car advertising discourse is based on function structure, i.e. subject (S), predicate (P), object (O), complement (Pel.), and adverb (K).This study aimed to describe simple sentence pattern variations in car advertising discourse based on word category in predicate and to describe compound sentence pattern variations in car advertising discourse based on its function structure. This research was a qualitative descriptive, namely research that describes, depicts or illustrates systematically. The object of this study was a single sentence and a compound in car advertisings in the Kedaulatan Rakyat, 2015. This research data was the variation of a single sentence and a compound in car advertising in the newspaper. Data collected used the method of direct observation, technical notes, and documentation. Data analysis techniques usedmethods agih. This research used techniques to change intentions, these techniques are always changing the form of one or several elements lingual related. Analysis of variation of the sentence in this research was the analysis of clause based on a function of its elements. Analisis variasi kalimat dalam penelitian ini merupakan analisis berdasarkan variasi pola kalimat tunggal dalam wacana iklan mobil berdasarkan kategori kata pada predikat, antara lain kalimat tunggal berpredikat verba, kalimat tunggal berpredikat adjektiva, kalimat tunggal berpredikat nomina, kalimat tunggal berpredikat frasa preposisi, dan kalimat tunggal berpredikat frasa numeralia. Analisis variasi pola kalimat majemuk dalam wacana iklan mobil berdasarkan struktur fungsinya, yaitu subjek (S), predikat (P), objek (O), pelengkap (Pel.), dan keterangan (K). Tujuan penelitian ini mendeskripsikan variasi pola kalimat tunggal dalam wacana iklan mobil berdasarkan kategori kata pada predikat dan mendeskripsikan variasi pola kalimat majemuk dalam wacana iklan mobil berdasarkan struktur fungsinya. Jenis penelitian ini adalah deskriptif kualitatif. Objek penelitian ini adalah kalimat tunggal dan majemuk dalam iklan mobil pada surat kabar Kedaulatan Rakyat edisi 2015. Data penelitian ini adalah variasi kalimat tunggal dan majemuk dalam iklan mobil di surat kabar. Pengumpulan data dilakukan dengan menggunakan metode observasi langsung, catatan teknis, dan dokumentasi. Teknik analisis datanya menggunakan metode agih. Teknik lanjutan penelitian ini menggunakan teknik ubah ujud, teknik ini selalu mengalami perubahan wujud salah satu atau beberapa unsur lingual yang berkaitan. Analisis variasi kalimat dalam penelitian ini adalah analisis klausa berdasarkan fungsi unsur-unsurnya.